2011
DOI: 10.1007/s00405-011-1485-2
|View full text |Cite
|
Sign up to set email alerts
|

Validity and accuracy of subciliary endoscopic-aided repair of orbital floor fractures

Abstract: 1b (individual inception study with >80% F/U).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
(37 reference statements)
0
1
0
1
Order By: Relevance
“…They concluded that the endoscopic aid allowed for better visualisation of the posterior extensions of the fracture. In addition, it also facilitated confirmation that all orbital soft tissues had been accurately elevated and that the graft had been properly positioned [19]. Within the orbital cavity, apart from the orbital floor, endoscopes are also being widely used in the repair of the medial wall and roof of the orbit [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the endoscopic aid allowed for better visualisation of the posterior extensions of the fracture. In addition, it also facilitated confirmation that all orbital soft tissues had been accurately elevated and that the graft had been properly positioned [19]. Within the orbital cavity, apart from the orbital floor, endoscopes are also being widely used in the repair of the medial wall and roof of the orbit [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Dependendo do tamanho do defeito, uma abordagem cirúrgica pode ser necessária. As fissuras muitas vezes podem ser tratadas de forma conservadora, enquanto que fraturas cominutivas e defeitos maiores requerem cirurgia para reconstrução do assoalho 8,9 . A seleção do material para reconstrução do AO está relacionada a diversos fatores, como: tamanho do defeito, paredes envolvidas, adaptação dos contornos internos, restauração do volume apropriado, tempo decorrido do trauma e experiência do cirurgião 10 .…”
Section: Introductionunclassified